The effects of short-term garlic supplementation on cardiopulmonary variables in healthy young sedentary males with hot nature. - معرفت سیاه‌کوهیان; آیلار ایمانی (Shahid Beheshti University, 2014)
Background: Various factors affecting the cardiopulmonary variables, particularly supplementation studies are considered. Garlic that is known as a medicinal plant for the treatment of cardiovascular and other metabolic diseases, include active photochemical units. Purpose: Purpose of this research was to investigate the acute effects of garlic supplementation on oxygen consumption volume (Vo2), carbon dioxide production volume (Vco2), respiratory exchange ratio (RER) and pulse oxygen (O2 pulse) among healthy young sedentary males with hot nature. Materials and Methods: Thirty healthy young sedentary males (Age 21.8 ± 1.75 yrs., Height 174.3 ± 1.8 cm, Weight 67.6 ± 3.4 kg) divided no randomly into two groups of supplementation and placebo. The supplement group received each day for a week 1000 mg of garlic pill and placebo group each day for a week 500 mg of starch. All of the subjects participated before and after supplementation on self-dependent exhaustive protocol. The cardiopulmonary variables of aerobic and anaerobic threshold and maximal state were measured with the respiratory gas analysis. Analysis of covariance (ANCOVA) as well as the Omega Square (w2) was used to analysis the data. Results: Our results indicate that taking garlic pill has a significant effect on maximal respiratory exchange ratio and anaerobic oxygen pulse. Conclusion: According to the results it could be concluded that short-term supplementation of garlic presumably affect on the maximal respiratory exchange ratio and anaerobic O2 pulse in the healthy. young sedentary males.